Skin or Skim? Inside Investment and Hedge Fund Performance - Gupta, Arpit; Sachdeva, Kunal (Management Science, 2025)
Hedge fund managers contribute substantial personal capital, or “skin in the game,” into their funds. Although these allocations may better align incentives, managers may also strategically allocate their private capital in ways that negatively affect outside investors. We find that funds with more inside investment outperform other funds within the same family. This relationship is driven by managerial decisions to invest their own capital in their least-scalable strategies and restrict the entry of new outsider capital into these funds. Our results suggest that insider capital may work as a rent-extraction mechanism at the expense of fund participation of outside investors. This paper was accepted by Gustavo Manso, finance. Funding: This work was supported by Columbia University and the Leonard N. Stern School of Business, New York University. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.4984 .